KEBERADAAN PAGUYUBAN SENI KARAWITAN KANTOR SETDA KABUPATEN BOYOLALI - Anggit Larasati; Nyoman Sukerna (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2019)
This article is motivated by the employees of the Boyolali District Secretariat who feel bored while working all day at the office. Boredom makes employees not focus on their work. Until in the end they found a solution to solve the problem, namely by having a context. According to them, having charisma can make the mood and mind calm, and from that the Andini Laras community association was formed which consisted of employees of the Boyolali District Secretariat. Based on this background, the problems revealed in this study are (1) How the activities of Setda Boyolali’s gamelan community since it was founded in 1988 until now and (2) Why the Setol regency’s gamelan musical community is still surviving until now. This research is a qualitative research, to answer this question the author uses Marx’s ideas about sociology and Sedyawati’s development. Based on observations, involvement and efforts were made to conduct mental therapy while preserving and preserving Javanese culture. Efforts are made to maintain its existence through activities based on member motivation and external stimulation. The members’ motivation was in the form of a desire to express their joy in music and their desire to do mental therapy. The stimulation that influenced the existence of the musical arts community of the Boyolali District Secretariat office remained in the form of community and government support in Boyolali Regency.Keywords: The existence, Andini Laras, and the Regional Secretariat Staff.